Correlation of P53 expression and epithelial-mesenchymal transition in non-small cell lung cancer - Xiangmei Wu; Lijiang Duan (Indian Journal of Pathology and Microbiology)
Background: Investigation of a potential prognostic marker expressed in non-small cell lung cancer (NSCLC) can help patients benefit from new target therapeuticmodalities. Aims: To study the expression and correlation of P53 protein and epithelial–mesenchymal transition (EMT) related makers in NSCLC. Materials and Methods: 32 cases were selected for immunohistochemistry analysis to evaluate the expression of P53 and EMT-related makers. Results: The positive expression rate of P53 and the incidence of EMT in NSCLC were closely linked to TNM stages, differentiation degree, and lymph node metastasis (P < 0.05). A positive association was found between P53 and EMT (r = 0.380, P < 0.05). Conclusions: There is a positive association between P53, snail, and EMT. P53 may affect EMT in NSCLC by up-regulating the expression of Snail and further promoting cancer invasion and metastasis.